Species diversity and distribution of schistosome intermediate snail hosts in The Gambia. - Ebrima Joof; Bakary Sanneh; Sana M Sambou; Christopher M Wade (Public Library of Science (PLoS), 2021)
There is a need for recent information on intermediate snail hosts of schistosomes in The Gambia; the previous studies were conducted over three decades ago. This study assessed the incidence, species diversity, distribution and infection status of schistosome intermediate snail hosts in the country. Malacological surveys were conducted in all 5 regions of The Gambia: Central River Region (CRR), Upper River Region (URR), Western Region (WR), Lower River Region (LRR) and North Bank Region (NBR). Sampling of snails was undertaken at 114 sites that included permanent water bodies such as streams (bolongs), rice fields, irrigation canals and swamps; and temporal (seasonal) laterite pools. Ecological and physicochemical factors of sites were recorded. Snails were identified morphologically and screened for schistosome infections using molecular techniques. Freshwater snails were found at more than 50% (60/114) of sites sampled. While three species of Bulinus were collected, no Biomphalaria snails were found in any of the sites sampled. Of the total 2877 Bulinus snails collected, 75.9% were identified as Bulinus senegalensis, 20.9% as Bulinus forskalii and 3.2% as Bulinus truncatus. Seasonal pools produced the largest number of snails, and CRR was the region with the largest number of snails. Bulinus senegalensis was found more in seasonal pools as opposed to permanent sites, where B. forskalii and B. truncatus were observed to thrive. Bulinus snails were more common in seasonal sites where aquatic vegetation was present. In permanent sites, the abundance of snails increased with increase in water temperature and decrease in water pH. Bulinus senegalensis was found infected with both S. haematobium and S. bovis, while B. forskalii and B. truncatus had only S. bovis infection. While the human parasite S. haematobium was restricted to just four sites, the livestock parasite S. bovis had a much more widespread geographical distribution across both CRR and URR. This new information on the distribution of intermediate snail hosts of schistosomes in The Gambia will be vital for the national schistosomiasis control initiative.